Corresponsabilidad familiar, prácticas organizacionales, equilibrio trabajo-familia y bienestar subjetivo en Chile. (2014)
The study of family responsibility has become more relevant in Chile. Research suggests that from the public and private sectors various initiatives towards the implementation of public policies that favor this inclusion are required. The global labor scene has changed considerably in the social, economic and family areas, exposing the need to reorganize the distribution of work responsibilities between men and women. As a contribution to the discussion, we analyze here the main background, and the need to review public policies, to implement the measures in the organizational field and to investigate further appropriate measures to Chile as a means to improve the quality of working life in the country.